Image-guided hypofractionated double-scattering proton therapy in the management of centrally-located early-stage non-small cell lung cancer. (2nd October 2020) - Kharod, Shivam M.; Nichols, R. Charles; Henderson, Randal H.; Morris, Christopher G.; Pham, Dat C.; Seeram, Vandana K.; Jones, Lisa M.; Antonio-Miranda, Maria; Huh, Soon; Li, Zuofeng; Hoppe, Bradford S.
Abstract: Background: The treatment of centrally-located early-stage non-small cell lung cancer (NSCLC) with image-guided stereotactic body radiotherapy (SBRT) is challenging due to the proximity of critical normal structures to the tumor target. The purpose of this study was to report the results of our experience in treating centrally-located early-stage NSCLC with hypofractionated proton therapy (PT). Material and methods: Between 2009 and 2018, 23 patients with T1–T2N0M0 NSCLC (T1, 46%; T2, 54%) were treated with image-guided hypofractionated double-scattering PT. The median age at the time of treatment was 74 years (range, 58–88). Patients underwent 4-dimensional computed tomography (CT) simulation following fiducial marker placement, and daily image guidance was performed. All patients were treated with 60 GyRBE in 10 fractions. Patients were assessed for CTCAEv4 toxicities weekly during treatment, and at regular follow-up intervals with CT imaging for tumor assessment. Overall survival, cause-specific survival, local control, regional control, and metastases-free survival were evaluated using cumulative incidence with competing risks. Results: Median follow-up for all patients was 3.2 years (range, 0.2–9.2 years). Overall survival rates at 3 and 5 years were 81% and 50% (95% CI, 27–79%), respectively. Cause-specific survival rates at 3 and 5 years were 81% and 71% (95% CI, 46–92%). The 3-year local, regional, and distant control rates were 90%, 81%, and 87%, respectively. Three patients (13%) experienced local recurrences as their first recurrence, at a median time of 28 months from completion of radiation (range, 18–61 months). Two patients (9%) experienced late grade 3 toxicities, including 1 patient who developed a bronchial stricture that required stent placement. Conclusion: Image-guided hypofractionated PT for centrally-located early-stage NSCLC provides excellent local control with low rates of grade ≥3 toxicities. For tumors in sensitive locations, PT may provide safer treatment than photon-based treatments due to its dosimetric advantages.